Developing a Kaupapa Māori Research Project to Help Reduce Health Disparities Experienced by Young Māori Women and Their Babies. Issue 3 (September 2013) - Lawton, Beverley; Cram, Fiona; Makowharemahihi, Charrissa; Ngata, Tina; Robson, Bridget; Brown, Selina; Campbell, Warahi
Young Māori mothers experience stigma and their babies experience poor health outcomes. Interventions to reduce these health disparities need to understand the lives of these young women. This paper describes consultation to seek agreement for research with young Māori mothers to be conducted in two regions. Consultation occurred with tribal authorities, Māori health providers, district health boards, and community stakeholders. Endorsement was gained for strength-based research with young pregnant Māori women and their babies. The research also includes service provider interviews, and analysis of policy. Project oversight is by three advisory groups: Māori elders, young Māori mothers, and an academic group. Community feedback occurs throughout the project. Consultation is an ongoing process conducted within a relationship context. It enhances the development, implementation and translation of research that seeks to represent the lives of those who are vulnerable, and eliminate health disparities.